FACTORS AFFECTING STUDENT'S DECISION USING SHARIA BANK PRODUCTS: A CASE STUDY IN IAIN KENDARI - Habun Khoirun Nisa; La Ode Alimusa; Zulkifli Zulkifli (Mega Aktiva, 2022)
This study investigates the factors that determine student decisions to use the product of the Indonesian Islamic Bank (BSI) case study on IAIN Kendari students. This research is based on several trends from previous research results in various Muslim countries. The research design is through a survey questionnaire and the analytical method to measure this goal is Exploratory Factor Analysis (EFA) with a sample of 100 samples with the criteria of students using savings products at Bank Syariah Indonesia (BSI). The results show that there are 3 main factors that determine the behaviour of students' decisions to use Islamic bank products, namely perceived Islamic value (halal product guarantees, interest-free products, Islamic services and ease of transactions), Islamic literacy (good understanding of Islamic banks, knowing the legal basis used by Islamic banks, and desires that arise from themselves) and institutional support (the collaboration of campuses and Islamic banks as well as determining student payment transactions through Islamic banks